SELF-COMPASSION: HOW DOES IT MODERATE THE EFFECT OF CULTURAL KNOWLEDGE ON PROSPECTIVE COUNSELORS' CULTURAL HUMILITY? - Nilna Aula Niswah; Antika, Eni Rindi (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
The phenomenon of the teacher marketplace requires prospective counselors of Semarang State University (UNNES) to improve competence in the field of culture, one of which is cultural humility. The inconsistency between the results of the counselor candidate interview and the measurement of counselees who practice with UNNES counselor candidates is the urgency of this study to examine the influence of cultural knowledge on cultural humility. This influence can be strengthened or weakened by intrinsic encouragement through self-compassion. This study aims to determine the effect of cultural knowledge on cultural humility in terms of self-compassion in UNNES counselor candidates. This study uses a quantitative approach with a correlation research design. The subjects of this study were 132 of the total population of 196 counseling students of the FIPP UNNES class of 2020 and 2021 who were selected using a proportionate stratified random sampling technique. The methods used are descriptive analysis, simple linear regression, and Moderated Regression Analysis (MRA). Based on the results of descriptive analysis, the cultural knowledge variable is in the medium category (M = 35.90 SD = 4.49), the cultural humility variable is in the high category (M = 53.04 SD = 4.80), and the self-compassion variable is in the medium category (M = 38.60 SD = 5.18). The results showed that cultural knowledge was proven to affect cultural humility by 34.7% and self-compassion had a moderating effect on the effect of cultural knowledge on cultural humility of UNNES counselor candidates by 51.6%. Referring to this, the researcher recommends further research to explore the demographic role of respondents and conduct causality or mixed method research that does not only use psychological scale measurement tools.